2022
DOI: 10.3390/ijms23179545
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-10a-5p Targeting the BCL6 Gene Regulates Proliferation, Differentiation and Apoptosis of Chicken Myoblasts

Abstract: Proliferation, differentiation, and apoptosis are three essential stages in cell development, and miRNAs can achieve extensive regulation of cellular developmental processes by repressing the expression of target genes. According to our previous RNA-seq results, miRNA-10a-5p was differentially expressed at different periods in chicken myoblasts, revealing a possible association with muscle development. In this study, we concluded that miRNA-10a-5p inhibited chicken myoblasts’ proliferation and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…First, the supernatant with single cells was inoculated into a 10-cm plate and placed the plate in the incubator. After 40 min, the supernatant was transferred to a new 10-cm dish, repeating the above steps 3 times to remove fibroblasts ( Li et al, 2018 ; Zhang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, the supernatant with single cells was inoculated into a 10-cm plate and placed the plate in the incubator. After 40 min, the supernatant was transferred to a new 10-cm dish, repeating the above steps 3 times to remove fibroblasts ( Li et al, 2018 ; Zhang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure 1A). 83−85 Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, 4−6 oxidative stress, 7 cell proliferation, 8,9 inflammation, 10,11 hematopoiesis, 4,12 and tumorigenesis. 13,14 Recent studies revealed that miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine.…”
Section: Micrornasmentioning
confidence: 99%
“…These functional miRNAs form the RISC via binding to AGO. Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure A). Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, oxidative stress, cell proliferation, , inflammation, , hematopoiesis, , and tumorigenesis. , …”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies confirmed that some regulatory genes have an essential impact in the incidence and development of IDD, such as microRNA (miRNA). The miRNA are single-stranded noncoding small RNA with 18 to 24 bp nucleotide sequences, which participates in regulating the cell proliferation and apoptosis [21][22][23][24][25]. And miRNA can negatively regulate the posttranscriptional gene expression in different species by either inhibiting mRNA translation or promoting mRNA degradation [25,26].…”
Section: Introductionmentioning
confidence: 99%